2012
DOI: 10.3897/zookeys.241.3831
|View full text |Cite
|
Sign up to set email alerts
|

A redescription of the leggiest animal, the millipede Illacme plenipes, with notes on its natural history and biogeography (Diplopoda, Siphonophorida, Siphonorhinidae)

Abstract: With up to 750 legs, the millipede Illacme plenipes Cook and Loomis, 1928 is the leggiest animal known on Earth. It is endemic to the northwestern foothills of the Gabilan Range in San Benito County, California, where it is the only known species of the family Siphonorhinidae in the Western Hemisphere. Illacme plenipes is only known from 3 localities in a 4.5 km2 area; the 1926 holotype locality is uncertain. Individuals of the species are strictly associated with large arkose sandstone boulders, and are extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 39 publications
(54 reference statements)
0
30
0
Order By: Relevance
“…The secretion of Petaserpes cryptocephalus (¼Polyzonium rosalbum in Meinwald et al, 1975); Polyzoniida, Polyzoniidae) is also sticky, which was attributed by Blum (1981) at least in part to the nitropolyzonimine component. Marek et al (2012) reported sticky material exuded by Illacme plenipes (Siphonophorida, Siphonorhinidae), but it appeared to come from metatergal setae, not the ozopores. In passing, Chamberlin (1923) remarked that another siphonophoridan (Siphonophora pearsi) could also produce sticky threads, but did not specify the source.…”
Section: Physical Actions Of Secretionsmentioning
confidence: 93%
“…The secretion of Petaserpes cryptocephalus (¼Polyzonium rosalbum in Meinwald et al, 1975); Polyzoniida, Polyzoniidae) is also sticky, which was attributed by Blum (1981) at least in part to the nitropolyzonimine component. Marek et al (2012) reported sticky material exuded by Illacme plenipes (Siphonophorida, Siphonorhinidae), but it appeared to come from metatergal setae, not the ozopores. In passing, Chamberlin (1923) remarked that another siphonophoridan (Siphonophora pearsi) could also produce sticky threads, but did not specify the source.…”
Section: Physical Actions Of Secretionsmentioning
confidence: 93%
“…al. 2003) according to the methods described in Marek et al (2012). Amplified DNA was confirmed with electrophoresis on a 10% agarose gel, and raw PCR amplicons were cleaned, quantified, and Sanger-sequenced at the University of Arizona Genomics Core on an ABI 3100 capillary DNA sequencer.…”
Section: Methodsmentioning
confidence: 99%
“…It has been implemented in several groups (ground beetles [4], termites [5], millipedes [6]) including earthworms: [7] used MaxEnt to study the effect of large-scale ecological variables in the distribution of Hormogaster elisae, corroborating its high predictive power and the ability to reflect accurately its soil preferences.…”
Section: Introductionmentioning
confidence: 99%